CULTURAL VALUES IN SONG LYRICS ENDENG-ENDENG IN WEDDING CEREMONY OF MANDAILING SOCIETY IN NORTH LABUHANBATU REGENCY - LIDYA UTAMI HARAHAP; ELISA BETTY MANULLANG; CITRA ANGGIA PUTRI (LINGUISTICA, 2021)
This study focused on finding out the cultural values in song lyrics Endeng- endeng of Mandailing society in North Labuhanbatu Regency. The objectives of this study were : (1) to find out the types of cultural values in song lyrics Endeng- endeng, (2) to find out the dominant types that used in song lyrics Endeng-endeng and (3) how the realization of the cultural values in wedding ceremony of Mandailing society in North Labuhanbatu Regency. This research was conducted by using descriptive qualitative design. There were 18 data of cultural values that were taken from song lyrics Endeng-endeng transcriptions. The findings of this research were : (1) There were nine cultural values of Batak that found in song lyrics Endeng-endeng, that contained kinship (16.7%), religion (16.7%), hagabeon (extended family)(11.1%), hasangapon (respect) (11.1%), hamoraon (wealth) (5.5%), hamajuon (modernization) (11.1%), patik dohot uhum (rules and laws) (11.1%), pangayoman (nurture) (5.5%) marsisarian (conflict) (11.1%). (2) The most dominant types of cultural value was kinship and religion (16.7%). (3) The realization of cultural values of song lyrics Endeng-endeng of Mandailing society in North Labuhanbatu Regency was described by interview the informants that understood about Endeng-endeng. The meanings in song lyrics Endeng- endeng were the advices for the groom that should be applied by them in their life after got marriage.